2019
DOI: 10.1186/s13075-018-1772-z
|View full text |Cite
|
Sign up to set email alerts
|

Non-inferiority of dose reduction versus standard dosing of TNF-inhibitors in axial spondyloarthritis

Abstract: ObjectiveThe objective was to determine if dose reduction is non-inferior to full-dose TNFi to maintain low disease activity (LDA) in patients already in remission with TNFi, in axial spondyloarthritis.MethodsRandomized, parallel, non-inferiority, open-label multicentre clinical trial. Patients were eligible if they had axial spondyloarthritis and had been in clinical remission for ≥ 6 months with any available TNFi (adalimumab, etanercept, infliximab, golimumab) at the dose recommended by product labelling. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 30 publications
1
42
0
Order By: Relevance
“…Furthermore, PsA and axSpA share pathophysiological, genetic and clinical characteristics, and as current treatment options are almost identical with respect to type of drugs used, dosing and concomitant DMARDs used (Table 1) and finally because preliminary dose optimisation data are similar, we felt this was possible without too much risk of Table 1 Overview of DMARDs in psoriatic arthritis, radiographic axial spondyloarthritis and non-radiographic axial spondyloarthritis different effects in the two diseases. The T2T principle is also already widely pursued in multiple chronic inflammatory disorders, including PsA and axSpA, indicating that this overarching principle seems disease agnostic [9,17,18,22]. Additionally, the outcome of non-inferiority of the tapering strategy is not dependent on the percentage of patients that can taper or stop, but on the implementation of the T2T strategy and the effectiveness of increased or restarted dosing on disease activity, and we do not anticipate effect modification between the two closely related diseases.…”
Section: Patientsmentioning
confidence: 81%
See 1 more Smart Citation
“…Furthermore, PsA and axSpA share pathophysiological, genetic and clinical characteristics, and as current treatment options are almost identical with respect to type of drugs used, dosing and concomitant DMARDs used (Table 1) and finally because preliminary dose optimisation data are similar, we felt this was possible without too much risk of Table 1 Overview of DMARDs in psoriatic arthritis, radiographic axial spondyloarthritis and non-radiographic axial spondyloarthritis different effects in the two diseases. The T2T principle is also already widely pursued in multiple chronic inflammatory disorders, including PsA and axSpA, indicating that this overarching principle seems disease agnostic [9,17,18,22]. Additionally, the outcome of non-inferiority of the tapering strategy is not dependent on the percentage of patients that can taper or stop, but on the implementation of the T2T strategy and the effectiveness of increased or restarted dosing on disease activity, and we do not anticipate effect modification between the two closely related diseases.…”
Section: Patientsmentioning
confidence: 81%
“…A randomised controlled non-inferiority trial reported by Gratacós et al demonstrated noninferiority between dose optimisation and full-dose TNFi treatment in patients with axSpA. However, TNFi treatment was reduced by 25% only, and the trial was lacking a sufficient disease activity-guided tapering algorithm [17]. A recent randomised controlled trial by Landewé et al in patients with non-radiographic axSpA (nraxSpA) raised two important points.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the recent EULAR guidelines [13] incorporate the tapering of biological therapy for these patients as a new recommendation, even though the data supporting this policy are limited due to the absence of randomized controlled studies. Recently our group have been communicated a randomized pragmatical study demonstrating the no inferiority of a regime of dose reduction compared with full doses in these patients [14].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the North American panel conditionally recommends against using a treat-to-target strategy based on the Ankylosing Spondylitis Disease Activity Score (ASDAS), which is in contrast with the European recommendations 5 Drug tapering has also been addressed in the 2019 ACR/SAA/SPARTAN update with a recommendation against tapering of the biologic dose as opposed to the ASAS-EULAR document where tapering was also considered and recommended. Despite literature being scarce in this field, successful tapering without significant relapses has been reported 7 . As more patients with axSpA are receiving biologic treatment and early intervention is encouraged, long term impact of continuous biologic therapy needs to be explored.…”
Section: News and Viewsmentioning
confidence: 99%